2010
DOI: 10.1242/jeb.045369
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting vagal feedback affects birdsong motor control

Abstract: SUMMARYCoordination of different motor systems for sound production involves the use of feedback mechanisms. Song production in oscines is a well-established animal model for studying learned vocal behavior. Whereas the online use of auditory feedback has been studied in the songbird model, very little is known about the role of other feedback mechanisms. Auditory feedback is required for the maintenance of stereotyped adult song. In addition, the use of somatosensory feedback to maintain pressure during song … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This result is very similar to that reported by Mendez et al, who reported that unilateral vagotomy of adult zebra finches caused alterations in the normal respiratory pattern during song, sometimes leading to acoustic changes such as truncations and interruptions (Mendez et al, 2010). These disruptions occurred within the first few days post-surgery, followed by partial or full recovery, and were highly variable between individual birds, as observed here.…”
Section: Resultssupporting
confidence: 91%
“…This result is very similar to that reported by Mendez et al, who reported that unilateral vagotomy of adult zebra finches caused alterations in the normal respiratory pattern during song, sometimes leading to acoustic changes such as truncations and interruptions (Mendez et al, 2010). These disruptions occurred within the first few days post-surgery, followed by partial or full recovery, and were highly variable between individual birds, as observed here.…”
Section: Resultssupporting
confidence: 91%
“…For 150-and 300-cent shifts, the fraction of compensation at the end of the shift epoch similarly decreased with shift size. Such incomplete learning could result from the bird's relying in part on nonauditory inputs such as proprioceptive feedback or the output of an internal model used to predict sensory feedback (13)(14)(15) (1,10). It is therefore unlikely that the plateau in vocal learning shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such a flexible weighting strategy might account for the inverse relationship between the size of sensory pitch shifts and the magnitude of the behavioral responses. That is, when experiencing large errors, songbirds might reduce their reliance on auditory information and increase their reliance on proprioceptive signals (13,14) or internal models of motor output (15) to estimate vocal pitch. The resulting integrated estimate might then be compared with an internal target to generate an error signal.…”
Section: Discussionmentioning
confidence: 99%
“…Because PAm receives a strong input from the lateral parasolitary nucleus (lPs) of nTS, it is conceivable that the transition from a minibreath to the generation of a new timing signal would be strongly influenced by vagal inputs that relay to PAm, via nTS, afferent signals regarding the internal state of the respiratory periphery (lungs, air sacs). This possibility has only recently been explored in songbirds (Mendez et al, 2010) and a general role for sensory input into vocal control is generally under appreciated. In cats, however, the general role of respiratory input within the context of vocalization, and the specific importance of pulmonary feedback for the ability to vocalize, was explored and demonstrated over 15 years ago (Davis and Zhang, 1996; Davis et al, 1996; Nakazawa et al, 1997).…”
Section: Song Production and The “Respiratory-thalamo-cortical” Patmentioning
confidence: 99%